2014
DOI: 10.1001/jama.2014.12360
|View full text |Cite
|
Sign up to set email alerts
|

Managing Posthospital Care Transitions for Older Adults

Abstract: In this issue of JAMA, Dhalla and colleagues 1 report findings from a randomized trial comparing the effect of usual care vs a "virtual ward" model of posthospital care management for older adults on reducing the primary end point of 30-day hospital readmissions. The virtual ward focused on care coordination by telephone or e-mail contact as well as clinic or home visits for several weeks following hospital discharge. With Medicare hospital reimbursement increasingly tied to 30day readmission rates, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…When transitional care is mishandled, the result is often higher levels of complications and likelihood of hospital readmission [73]. Almost one fifth of Medicare patients discharged from a hospital require another hospitalization within 30 days due to an acute medical problem [74].…”
Section: Nutritional Risks In the Hospital Setting And Care Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When transitional care is mishandled, the result is often higher levels of complications and likelihood of hospital readmission [73]. Almost one fifth of Medicare patients discharged from a hospital require another hospitalization within 30 days due to an acute medical problem [74].…”
Section: Nutritional Risks In the Hospital Setting And Care Transitionsmentioning
confidence: 99%
“…Another high-risk situation for older adults occurs when they are receiving transitional care, the care they need when they “move from one care site to another” [72]. When transitional care is mishandled, the result is often higher levels of complications and likelihood of hospital readmission [73]. Almost one fifth of Medicare patients discharged from a hospital require another hospitalization within 30 days due to an acute medical problem [74].…”
Section: Nutritional Risks In the Hospital Setting And Care Transitionsmentioning
confidence: 99%
“…In recent years, some studies have suggested that special care programs can be partially effective in reducing re-hospitalizations (37)(38)(39). The striking issue in these studies is that an organization that is applicable to elderly care-related situations, specific to patients with a high risk of complications, does not exist.…”
Section: How Can High-risk Patients Be Detected?mentioning
confidence: 99%
“…Care transitions are associated with myriad challenges for clinicians and patients. Older adults in particular are at increased risk for medical errors, communication gaps, and unplanned readmission during posthospitalization care transitions . The Centers for Medicare & Medicaid Services has implemented new policies and payment models aimed at improving posthospitalization care transition quality, including the Hospital Readmissions Reduction Program, Bundled Payments for Care Improvement, and transitional care management billing codes…”
Section: Introductionmentioning
confidence: 99%